2009
DOI: 10.1108/09513540910933521
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' organisational behaviour in public and private funded schools

Abstract: PurposeThe purpose of this paper is to compare teachers' organisational behaviour in publicly‐ and privately‐funded schools in the Dutch Vocational Education and Training (VET) sector.Design/methodology/approachA percentage of all middle managers in publicly and privately funded schools (72 per cent and 43 per cent respectively) distributed self‐report questionnaires to their teachers measuring teachers' attitudes, sense of identification and perception of the school climate. The sample consisted of 705 teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Goulet and Frank (2002) compared employees in public, non-profit and for-profit organizations, and found that private sector employees were the most identified with their organizations. Similarly, Honingh and Oort (2009) found that teachers in privately funded schools in the vocational sector identified with their schools more than their colleagues working in publicly funded schools. Feather and Rauter (2004) also found that organizational citizenship behavior was higher in private schools in comparison to that of the public schools.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Goulet and Frank (2002) compared employees in public, non-profit and for-profit organizations, and found that private sector employees were the most identified with their organizations. Similarly, Honingh and Oort (2009) found that teachers in privately funded schools in the vocational sector identified with their schools more than their colleagues working in publicly funded schools. Feather and Rauter (2004) also found that organizational citizenship behavior was higher in private schools in comparison to that of the public schools.…”
Section: Resultsmentioning
confidence: 95%
“…Teachers' job status has a statistically significant effect on both organizational citizenship behaviors and organizational identification. Honingh and Oort (2009) have stated organizational behavior of employees in public sector and private sector organizations differs. For instance because of difference in monitoring and evaluation of performance, the visibility of individual efforts in private schools is higher than public schools.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In analysing the extent to which teachers have a goal-oriented attitude, Honingh and Oort (2008) found a significant difference between teachers in privately and publicly funded schools. Teachers working in privately funded schools had a stronger goal-oriented attitude.…”
Section: Differences Among Teachersmentioning
confidence: 99%
“…In a recent study Honingh and Oort (2008) investigated teachers' attitudes to education in three disciplinary branches: catering and tourism, health and social care and economics and administration, 5 in publicly and privately funded schools in the Dutch VET sector. The items in the questionnaire were based on Denessen's (1999) questionnaire measuring secondary school teachers' attitudes to education.…”
Section: Teachers' Attitudes To Education In Publicly and Privately F...mentioning
confidence: 99%